Estrogen receptor signaling in prostate cancer: Implications for carcinogenesis and tumor progression - Bonkhoff, Helmut (The Prostate, 2018)
Background The androgen receptor (AR) is the classical target for prostate cancer prevention and treatment, but more recently estrogens and their receptors have also been implicated in prostate cancer development and tumor progression. Methods Recent experimental and clinical data were reviewed to elucidate pathogenetic mechanisms how estrogens and their receptors may affect prostate carcinogenesis and tumor progression. Results The estrogen receptor beta (ERβ) is the most prevalent ER in the human prostate, while the estrogen receptor alpha (ERα) is restricted to basal cells of the prostatic epithelium and stromal cells. In high grade prostatic intraepithelial neoplasia (HGPIN), the ERα is up‐regulated and most likely mediates carcinogenic effects of estradiol as demonstrated in animal models. The partial loss of the ERβ in HGPIN indicates that the ERβ acts as a tumor suppressor. The tumor promoting function of the TMPRSS2‐ERG fusion, a major driver of prostate carcinogenesis, is triggered by the ERα and repressed by the ERβ. The ERβ is generally retained in hormone naïve and metastatic prostate cancer, but is partially lost in castration resistant disease. The progressive emergence of the ERα and ERα‐regulated genes (eg, progesterone receptor (PR), PS2, TMPRSS2‐ERG fusion, and NEAT1) during prostate cancer progression and hormone refractory disease suggests that these tumors can bypass the AR by using estrogens and progestins for their growth. In addition, nongenomic estrogen signaling pathways mediated by orphan receptors (eg, GPR30 and ERRα) has also been implicated in prostate cancer progression. Conclusions Increasing evidences demonstrate that local estrogen signaling mechanisms are required for prostate carcinogenesis and tumor progression. Despite the recent progress in this research topic, the translation of the current information into potential therapeutic applications remains highly challenging and clearly warrants further investigation.